THE 'TRUMP EFFECT' ON POLITICAL CONTENT BY FAR-RIGHT AUDIENCES ON PORTUGUESE-LANGUAGE YOUTUBE CHANNELS - dos Santos, João Guilherme Bastos; Dourado, Tatiana; Amaral, Inês; Jerónimo, Pedro; Dienstbach, Dalby; Dugno, Alex; Torre, Luisa (AoIR Selected Papers of Internet Research, 2026)
This paper examines the transnational influence of far-right ideologies emanating from the United States, focusing on the figure of Donald Trump and his resonance within Portuguese-speaking YouTube communities. The study analyses 9,852 search results, encompassing 2,746 unique videos collected between October 15 and November 6, 2024. It identifies how political content and news narratives related to Trump are consumed and disseminated among far-right audiences in Brazil and Portugal. A significant finding is the role of YouTube's algorithm in prioritizing far-right content, which profoundly impacts the thematic narratives and sources that creators leverage to construct political discourses around Trump. Despite most videos being in English (89.01%), a notable subset (5.43%) were in Portuguese, predominantly from Brazilian channels, with only two Portuguese channels identified. The findings of this study have significant implications for understanding transnational far-right movements. The study reveals that the Brazilian YouTube ecosystem is characterized by themes of economic liberalism and financial prosperity, with moral conservatism notably absent. Comment analysis highlights narratives framing Trump as a divinely chosen leader, with parallels drawn to Jair Bolsonaro. Videos in the Portuguese language are mainly short, mobile-oriented productions, emphasizing economic commentary over traditional political rhetoric. The research underscores the role of digital platforms in fostering transnational far-right cohesion, exploring shared ideological and strategic alignments across Portuguese-speaking communities.